The contribution of informal learning in the integration process of immigrants into the labour market: Individual and organisational perspectives in selected sectors - Annen, Silvia [Verfasser] (My University, 2023)
„In Germany and Canada, the integration of immigrantsinto the labour market is closely related to the various approaches towards the recognition and validation of informal learning. This paper aims to analyse theinformal learning measures undertaken by immigrantsas well as those offered by employers in the health and information and communication technology sectors during the labour market integration process. The study focused on nurses as well as IT project managersand programmers. The comparison focuses on the occurrence and quality of the four dimensions of the dynamic model of informal learning from an individual and an organisation perspective. The results show similarities between these two perspectives regarding the relevance of the four dimensions in the integration of immigrants into the labour market. In addition, clear differences between the two investigated sectors as well as country‐specific differences appear.“ (author’s abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; L 2.1.1 Informelles Lernen; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.3.2 Nordamerika; 370; 330; Arbeitsmigration; Einwanderung; Einwanderer; Informelle Kompetenz; Informelles Lernen; Auslandsqualifikation; Anerkennung; Gesundheitswesen; Informationswirtschaft; Fallstudie; Fallstudie; Kanada; Bundesrepublik Deutschland; Learning Analytics